Building a Modular Creative Economy Assessment System with a Domain-Driven Design Approach and Agile Development - Zulfiandri Zulfiandri; Sarip Hidayatuloh; Muhammad Asyraf Faiz Kamil (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2026)
The creative economy assessment program involves high domain complexity and multi-stakeholder workflows that conventional content management systems fail to accommodate adequately. This paper presents the development of a Domain-Driven Design (DDD)-based Content Management System (CMS) for the creative economy assessment program, integrated with Agile (Scrum) development methodology. The study employed strategic DDD design including bounded context identification, ubiquitous language definition, and context mapping, followed by tactical design comprising entity, value object, aggregate, domain service, domain event, and repository pattern specifications. A Headless CMS architecture using Laravel 10 as the backend API and Next.js 15 as the frontend was implemented across four sprint cycles, resulting in a modular, maintainable system with clear domain separation. The system successfully modeled four bounded contexts (Borang Management, Assessment, User Management, Notification) and implemented Clean Architecture layering validated through Deptrac. Results demonstrate that the DDD approach effectively addresses creative economy assessment domain complexity, enabling independent development and testing of each bounded context while maintaining business rule integrity through aggregate design and domain events.